(untitled) (Medico Legal Update, 2020)
Purpose: Total antioxidant capacity (TAC) in women serum and follicular fluid (FF) which surrounding oocytes may be related to the implantation failure .Therefore, we herein examined the relationship between total antioxidant capacity status in serum and FFand it is association with implantation failure Method: One hundred and seventeen of non-reproductive women who underwent intra-cytoplasmic sperm injection (ICSI)included in this study and conducted between March 2018 and April 2019 in Kamal ALSamarai Hospital, center of fertility and IVF. Serum and follicular fluid were collected from non-reproductive women aged ranged 20-45 years and BMI (ranged 21.9-36.3kg/m2), TAC were measured using sandwich ELISA in serum and follicular fluid specimen of 21 women of successful implantation compared to 96 experienced implantation failures. Results: TAC was increased in serum of implantation failure compared to successful but not significant differences between two study groups. Whereas TAC levels were highly significant (P=0.002) inFF of women who had successful implantation (1.08 ± 0.64mmol/L) whereas in failure were lower(0.55 ± 0.42 mmol/L). In addition to that, when evaluating the frequency of TAC category in FF revealed highly significant differences (P=0.003) between two groups, the majority of failure groups(84.4%) had low TAC compared with (40%) in successful groups, while a significant increase of sufficient TAC in successful than failure groups (50% versus 6.1% respectively), whereas the borderline TAC were (9.1% versus 10%) in failure and successful groups. Conclusions: TAC in FF may be potential markers for implantation successful in ICSI cycle.